Residual interfragmentary gap after intramedullary nailing of fragility fractures of the humeral diaphysis: short and midterm term results - Ferrara, Fabrizio; Biancardi, Elena; Touloupakis, Georgios; Bibiano, Luigi; Ghirardelli, Stefano; Antonini, Guido; Crippa, Cornelio (Acta Biomedica Atenei Parmensis, 2019)
The purpose of this retrospective study was to evaluate the short and midterm radiological outcome with regards to bone healing, correlated with humeral shaft fractures treated with anterograde intramedullary nailing, when interfragmentary gap was significant. Here, we critically review our experience of short and midterm term results in over 65 year-old patients. Inclusion criteria in the study were: (1) patients over 65 years old (2) patients with displaced humeral mid shaft fractures (AO/OTA 12 A B C type fractures); (3) patients treated with closed reduction and internal fixation with intramedullary nail (Trigen Humeral Nail® Smith and Nephew) with at least two screws for proximal locking and one screw for distal locking; (4) residual interfragmentary gap, being considered significant any gap >6 mm (being 7 mm the minimum nail diameter available in our facility). Various factors were considered in our analysis: the size of the interfragmentary gap in both projections (also the mean of the measured gaps was calculated), the relationship between the greater and the mean interfragmentary gap and the second diameter measurement of the nail in the half distal part, the number of the screws in distal locking procedure, the use of a reaming procedure or not, the AO classification, the actual age at the time of surgery, the operating time, the nail second diameter as described before and its ratio with the measured residual gap. At 3 months follow-up, 4 patients showed radiographic healing (26,67%), 9 patients showed a visible callus (60%), with a total of 13 patients (86,67%) showing signs of normal recovery, the remaining 2 patient had insufficient callus formation (13,3%). At 6 months follow-up, 1 patient was missing (6,67%), although radiographic healing was already evident during the previous follow-up check, another one showed incomplete callus formation, the remaining 13 patients showed radiographic healing (86,67%), with a total of 14 patient considered healed at 6 months follow-up (93,33%). In conclusion, osteosynthesis with anterograde nail in geriatric patients appears to be a quite safe approach despite a great interfragmentary gap. After 6 months of treatment, callus formation and the overall clinical outcome were proven to be above satisfaction. (www.actabiomedica.it)